2012
DOI: 10.1371/journal.pone.0036191
|View full text |Cite
|
Sign up to set email alerts
|

Concordant Signaling Pathways Produced by Pesticide Exposure in Mice Correspond to Pathways Identified in Human Parkinson's Disease

Abstract: Parkinson's disease (PD) is a neurodegenerative disease in which the etiology of 90 percent of the patients is unknown. Pesticide exposure is a major risk factor for PD, and paraquat (PQ), pyridaben (PY) and maneb (MN) are amongst the most widely used pesticides. We studied mRNA expression using transcriptome sequencing (RNA-Seq) in the ventral midbrain (VMB) and striatum (STR) of PQ, PY and paraquat+maneb (MNPQ) treated mice, followed by pathway analysis. We found concordance of signaling pathways between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 65 publications
6
33
0
Order By: Relevance
“…Genes involved in fibrogenesis and stricture formation [54], [55], including collagen type I alpha (COL1A1), matrix metallopeptidase 3 (MMP3) and TIMP metallopeptidase inhibitor 1 and 2 (TIMP1 and TIMP2) are examples thereof. These findings are consistent with other comparative assessments of human disease and animal models [56], [57]. Our group has shown that the REG family proteins and CXCL10 are up-regulated in IBD [58], [59].…”
Section: Discussionsupporting
confidence: 91%
“…Genes involved in fibrogenesis and stricture formation [54], [55], including collagen type I alpha (COL1A1), matrix metallopeptidase 3 (MMP3) and TIMP metallopeptidase inhibitor 1 and 2 (TIMP1 and TIMP2) are examples thereof. These findings are consistent with other comparative assessments of human disease and animal models [56], [57]. Our group has shown that the REG family proteins and CXCL10 are up-regulated in IBD [58], [59].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, Wnt signalling is vital for adult neurogenesis [70] and for the normal function of mature neurones [71, 72]. Since the neuroprotective capacity of canonical Wnt signalling is also well described [27, 71, 73] and altered Wnt signalling has already been reported in the brains of PD patients and model animals [7476], modifying Wnt activity is evidently a plausible therapeutic strategy for PD.…”
Section: Discussionmentioning
confidence: 99%
“…But a recent study has reported that pyridaben exposure induced a 24% TH neuronal loss in the substantia nigra (SN) of mice. The authors also performed an RNAseq analysis and reported that mice exposed to certain pesticides exhibited gene expression patterns bearing significant correspondence to pathways that were well-known in human PD cases (Gollamudi et al, 2012). The results reported above have important implications about the neurotoxicological effects that tebufenpyrad and pyridaben might have on animal and human dopaminergic neuronal systems.…”
Section: Discussionmentioning
confidence: 99%